2016
DOI: 10.1210/en.2016-1315
|View full text |Cite
|
Sign up to set email alerts
|

Igf Binding Proteins Protect Undifferentiated Spermatogonia in the Zebrafish Testis Against Excessive Differentiation

Abstract: IGF binding proteins (IGFBPs) modulate the availability of IGFs for their cognate receptors. In zebrafish testes, IGF3 promotes the proliferation and differentiation of type A undifferentiated (A) spermatogonia, and igf3 expression is strongly elevated by FSH but also responds to T. Here we report the effects of FSH and T on igfbp transcript levels in adult zebrafish testis. We then examined T and FSH effects on zebrafish spermatogenesis and explored the relevance of IGFBPs in modulating these T or FSH effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 61 publications
3
44
0
2
Order By: Relevance
“…Fsh promotes spermatogenesis by modulating LC (fishspecific, in context with the presence of the Fshr on LCs) and SC (in all vertebrates, in context with the presence of the Fshr on SCs) functions. A previous study showed that zebrafish Fsh activated, in an androgen-independent manner, the differentiating proliferation of type A spermatogonia, but did not change the proportion of A und while increasing the one for A diff spermatogonia (Safian et al 2016). However, it was not known how Fsh acts to prevent depletion of type A und spermatogonia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fsh promotes spermatogenesis by modulating LC (fishspecific, in context with the presence of the Fshr on LCs) and SC (in all vertebrates, in context with the presence of the Fshr on SCs) functions. A previous study showed that zebrafish Fsh activated, in an androgen-independent manner, the differentiating proliferation of type A spermatogonia, but did not change the proportion of A und while increasing the one for A diff spermatogonia (Safian et al 2016). However, it was not known how Fsh acts to prevent depletion of type A und spermatogonia.…”
Section: Discussionmentioning
confidence: 97%
“…We have reported previously that 100 ng/mL Fshstimulated both self-renewal division of A und and differentiating proliferation toward A diff spermatogonia (Nóbrega et al 2015, Safian et al 2016, the latter by activating β-catenin signaling via Igf3 (Safian et al 2018). To study the potential involvement of Wnt signaling in A und proliferation and accumulation (i.e.…”
Section: Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Because Pappaa acts to increase IGF1 bioavailability by freeing IGF1 from IGFBPs (Boldt and Conover, 2007), we asked whether this role was important for hair cell survival following neomycin exposure. To test this, we bathed wild type and pappaa p170 larvae in NBI-31772, an IGFBP inhibitor that stimulates IGF1 availability (Safian et al, 2016). Treatment with NBI-31772 for 24 hours prior to and during neomycin exposure improved hair cell survival in wild type and pappaa p170 larvae (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…In male zebrafish, igf-3 promotes the proliferation and differentiation of type A undifferentiated spermatogonia. In a study by Safian et al (2016), an increase in igfbp-3 lead to a decrease in type A undifferentiated spermatogonia, the primary cells involved in spermatogenesis (De Paiva Camargo et al 2017). Further research indicated that igfbp-3 and igfbp-5 have opposing effects on controlling igf-3 bioactivity in zebrafish (Safian et al 2016).…”
Section: Discussionmentioning
confidence: 95%